Nephrologists' and nephrology nurses' design preferences for a wearable dialysis device. (September 2022) - Anna Jónsdóttir, Auður; Lazo, Gabrielle R.; Sundar, Sahana; Kessler, Larry; Kim, Ji-Eun
The objective of thisstudy is to characterize nephrology nurses' and nephrologists' design expectations and preferences for a wearable dialysis device that allows a dialysis patient greater mobility and improved independence. We gathered ideal design characteristics, acceptable size and weight parameters, and the most preferred design type of a wearable dialysis device. Using qualitative analysis of open-ended questions and quantitative analysis of rank-order questions, our results indicate seven categories of ideal design features and give an estimate of parameters for the largest acceptable size and heaviest acceptable weight of the device. Furthermore, our results show that the clinicians significantly prefer a belt design over a shoulder bag, a vest, or a distributed design type. The findings from this study offer a vision for design preferences and usability objectives to help ensure users' safe and efficient use of a wearable dialysis device.